ISLAMIC STYLE IN LANDSCAPE DESIGN ON THE EXAMPLE OF ANCIENT GARDENS OF THE TEMURID PERIOD - Makhmudova, Malika; Makhmudova, Muhayyo (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article considers the history of the creation and development of the Islamic garden, the characteristic features of landscape gardening art in the Islamic style through the prism of the development of ancient gardens of the Temurid period, in particular, on examples of gardens in Central Asia, Afghanistan and India, and other countries, including their perspectives development, as well as proposals for the creation of modern landscape design. Today, with the urbanization and the growth of cities, less territory remains for the green zone, therefore one of the main problems throughout the world is the preservation of the environment, and especially landscape architecture. Gardening art has come a long way and many masterpieces have been irretrievably lost. Today, all aspects of the history and development of Islamic-style gardens and parks are still not disclosed. For this reason the issue of studying traditional Islamic-style gardens and, of course, reviving the traditional park-building culture of the Temurids and Baburids era was raised in Uzbekistan to create a green environment of historical sites and national parks. As a result of the research, the following were considered and identified: the history of the development of Islamic landscape design, the types of gardens in the Islamic style, the history of the creation of various gardens, their names, planning and compositional solutions, characteristic features, decorative techniques for building gardens in Central Asia, Afghanistan, India, technical and water devices used in the Temurid Gardens, as well as the importance of the Temurids dynasty in creating gardens and parks in Afghanistan and India. The conducted research, the experience of designing and creating Islamic gardens in Central Asia, Afghanistan, India and other countries will allow using the recommendations aimed at creating a modern garden in the Islamic style not only in Uzbekistan, but in other countries.